2014
DOI: 10.7314/apjcp.2014.15.5.2035
|View full text |Cite
|
Sign up to set email alerts
|

Lack of any Association of the CTLA-4 +49 G/A Polymorphism with Breast Cancer Risk in a North Indian Population

Abstract: Cytotoxic T-lymphocyte antigen 4 (CTLA-4) is an important protein involved in the regulation of the immune system. The +49 G/A polymorphism is the only genetic variation in the CTLA-4 gene that causes an amino acid change in the resulting protein. It is therefore the most extensively studied polymorphism among all CTLA-4 genetic variants and contributions to increasing the likelihood of developing cancer are well known in various populations, especially Asians. However, there have hiterto been no data with res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
0
6
1
Order By: Relevance
“…1B). However, some studies showed that lack of association between CTLA-4 polymorphisms and some types of cancer, including esophageal cancer in a Chinese population [57,58] and breast cancer in a North Indian population [59]. It is required to confirm the findings in large-scale and multi-populations studies.…”
Section: Ctla-4 Polymorphisms In Cancermentioning
confidence: 99%
“…1B). However, some studies showed that lack of association between CTLA-4 polymorphisms and some types of cancer, including esophageal cancer in a Chinese population [57,58] and breast cancer in a North Indian population [59]. It is required to confirm the findings in large-scale and multi-populations studies.…”
Section: Ctla-4 Polymorphisms In Cancermentioning
confidence: 99%
“…Numerous investigations have demonstrated that CTLA-4 genetic polymorphisms may have association with human breast cancer susceptibility (Erfani et al, 2006; Ghaderi et al, 2004; Li et al, 2012; Li et al, 2008; Minhas et al, 2014; Sun et al, 2008; Wang et al, 2007; Zhifu et al, 2015; Kong, 2010). The results showed that some of the polymorphisms such as rs733618 and rs4553808 may increase the breast cancer risk while other polymorphisms such as rs231775 and rs3087243 may reduce the risk of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…CTLA-4 gene is located in several immune regulatory gene areas of human chromosome 2q33 to 2q37 and contains many single nucleotide polymorphisms in the CTLA-4 gene. Among these polymorphisms, CTLA-4 A49G was widely studied and have been reported to be associated with the susceptibility of diverse human diseases (Cozar et al, 2007;Wang et al, 2007;Dilmec et al, 2008;Minhas et al, 2014). Some studies have reported the association between CTLA-4 A49G polymorphism and colorectal cancer; however, the results are conflicting (Solerio et al, 2005;Hadinia et al, 2007;Qi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%